2001
DOI: 10.1002/biof.5520140114
|View full text |Cite
|
Sign up to set email alerts
|

Functions of GI‐GPx: Lessons from selenium‐dependent expression and intracellular localization

Abstract: Gastro intestinal glutathione peroxidase (GI-GPx) is one of the four distinct mammalian selenoperoxidases. It had been reported to be restricted to the gastrointestinal tract but has more recently been identified also in human liver and some tumor cell lines. GI-GPx ranks high in the hierarchy of selenoproteins. The GI-GPx mRNA rather increases than decreases in selenium deficiency. GI-GPx protein responds poorly to selenium deprivation and increases fast upon resupplementation. Putative biological roles of GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…(i) GI-GPx mRNA is extremely stable in selenium deficiency, which ranks GI-GPx high in the hierarchy of selenoproteins and, thus, points to more vital functions than those the low-ranking selenoproteins such as cGPx may have (45,65). (ii) In accordance with the high mRNA stability, GI-GPx protein is synthesized first upon selenium resupplementation, while cGPx follows with a delay of at least 24 h, as has been demonstrated in vitro and in vivo (10,66). (iii) Unlike cGPx, GI-GPx is not uniformly expressed along the crypt-tovillus axis but is preferentially located in the crypts (22).…”
mentioning
confidence: 72%
“…(i) GI-GPx mRNA is extremely stable in selenium deficiency, which ranks GI-GPx high in the hierarchy of selenoproteins and, thus, points to more vital functions than those the low-ranking selenoproteins such as cGPx may have (45,65). (ii) In accordance with the high mRNA stability, GI-GPx protein is synthesized first upon selenium resupplementation, while cGPx follows with a delay of at least 24 h, as has been demonstrated in vitro and in vivo (10,66). (iii) Unlike cGPx, GI-GPx is not uniformly expressed along the crypt-tovillus axis but is preferentially located in the crypts (22).…”
mentioning
confidence: 72%
“…The role played by this enzyme in cancer remains obscure, but a recent study suggested an association between GST M4 polymorphisms and lung cancer risk, implying that the activity of this enzyme might be involved in tumour development [23]. GSH peroxidase 2 mRNA was also found to be more frequently expressed in tumour as compared to normal breast tissue; this enzyme can protect cells from free radicals and also regulate proliferation and apoptosis through redox signalling [24] and thus its increased expression may confer a survival advantage to tumour cells. Expression of GSH peroxidase 2 has been established in breast tissue [25] and increased expression of this enzyme has recently been reported in lung adenocarcinomas and in normal alveolar epithelium from smokers as compared to normal lung tissue from non-smokers [26].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the gastrointestinal tract expresses all four common GPX (GPX1-GPX4), which may suggest a significant role in colonic function (e.g., as a barrier for reactive oxygen species; refs. 26,31,32). Support for the importance of these selenoenzymes comes from an animal study showing that targeted disruption of both cytosolic and gastrointestinal GPX (GPX1 and GPX2, respectively) genes results in accumulation of lipid hydroperoxides (33) and high susceptibility to inflammation and colon cancer in mice (25,34).…”
Section: Introductionmentioning
confidence: 99%